Validation of the SarQoL®, a specific health‐related quality of life questionnaire for Sarcopenia. Issue 2 (22nd October 2016) - Beaudart, Charlotte; Biver, Emmanuel; Reginster, Jean‐Yves; Rizzoli, René; Rolland, Yves; Bautmans, Ivan; Petermans, Jean; Gillain, Sophie; Buckinx, Fanny; Dardenne, Nadia; Bruyère, Olivier
Abstract: Background: A specific self‐administrated health‐related quality of life questionnaire for sarcopenia, theSar copenia andQ ualityO fL ife (SarQoL®), has been recently developed. This questionnaire is composed of 55 items translated into 22 questions and organized into seven domains of quality of life. The objective of the present work is to evaluate the psychometric properties (discriminative power, validity, reliability, floor and ceiling effects) of the SarQoL® questionnaire. Methods: Sarcopenic subjects were recruited in an outpatient clinic in Liège, Belgium and were diagnosed according to the algorithm developed by the European Working Group on Sarcopenia in Older People. We compared the score of the SarQoL® between sarcopenic and non‐sarcopenic subjects using a logistic regression after adjustment for potential confounding variables. Internal consistency reliability was determined using Cronbach's alpha coefficient; construct validity was assessed using convergent and divergent validities. Test–retest reliability was verified after a two‐week interval using the intra‐class correlation coefficient (ICC). At last, floor and ceiling effects were also tested. Results: A total of 296 subjects with a median age of 73.3 (68.9–78.6) years were recruited for this study. Among them, 43 were diagnosed sarcopenic. After adjustment for potential confounding factors, the total score and the scores of the different dimensions of the SarQoL® questionnaire were significantly lower for sarcopenic than for non‐sarcopenic subjects (54.7 (45.9–66.3) for sarcopenic vs. 67.8 (57.3 – 79.0) for non sarcopenic, OR 0.93 (95%CI 0.90–0.96)). Regarding internal consistency, the Cronbach's alpha coefficient was 0.87. The SarQoL® questionnaire data showed good correlation with some domains of the Short‐Form 36 (SF‐36) and the EuroQoL 5‐dimension (EQ‐5D) questionnaires and with the mobility test. An excellent agreement between the test and the retest was found with an ICC of 0.91 (95% CI 0.82–0.95). At last, neither floor nor ceiling effects were detected. Conclusions: The SarQoL® questionnaire is valid, consistent, and reliable and can therefore be recommended for clinical and research purposes. However, its sensitivity to change needs to be assessed in future longitudinal studies.